Ensuring Transparency of ESG Transformation of Corporations (Using the Example of Retail Companies) - B. S. Bataeva (Управленческие науки)
In recent years, companies in the retail sector have begun to introduce and incorporate the principles of sustainable development into their strategies and began to publish reports on sustainable development. ESG transformation of companies in the retail industry has its own characteristics. The purpose of the work is to determine the directions of ESG transformation in retail companies, as well as tools for ensuring transparency of activities in the field of sustainable development. The methodological basis of the study was the concept of sustainable development and ESG, methods of statistical analysis, a systematic approach, scientific works of leading domestic and foreign scientists in the field of sustainable development, ESG transformation of retail companies. In the course of the work the author has identified 6 areas of ESG transformation that are most relevant and consistent with the Sustainable Development Goals and the industry specifics of the retail sector. It was revealed that there is a problem of comparability of ESG ratings and rankings from various agencies, insufficient prevalence of the practice of publishing non-financial reporting by organisations from this segment.The set of non-financial indicators proposed by the author for retail companies are grouped by areas of ESG transformation, as well as by Sustainable Development Goals. The publication of the proposed indicators in the annual report or sustainability report is intended to help management and interested stakeholders evaluate the results of ESG transformation of retail companies in more depth and detail.